A RESILIENCE LENS ON HOMELESS OLDER PERSONS IN THE CITY OF TSHWANE: AN ILLUMINATION THROUGH PHOTOVOICE - Jacobs, Leoné; Geyer, Stephan (Social Work/Maatskaplike Werk, 2022)
This qualitative study explores and describes the resilience of homeless older persons in the City of Tshwane, South Africa. Eleven participants, recruited purposively, participated in photovoice activities supplemented with semi-structured interviews. Data were analysed through reflexive thematic analysis and trustworthiness was ensured. Findings indicate that conflict, abuse, family disappointment, unemployment, mental health challenges, declining mobility, isolation and a lack of access to services are risk factors hindering resilience. Religion, support and socialisation, amongst other things, are identified as protective factors enabling resilience. Recommendations for resilience-informed biopsychosocial gerontological social services to homeless older persons are offered to navigate towards better-than-expected outcomes.